Mechanisms of acid tolerance in bacteria and prospects in biotechnology and bioremediation - Liu, Yuping; Tang, Hongzhi; Lin, Zhanglin; Xu, Ping (Biotechnology advances, 2015)
Acidogenic and aciduric bacteria have developed several survival systems in various acidic environments to prevent cell damage due to acid stress such as that on the human gastric surface and in the fermentation medium used for industrial production of acidic products. Common mechanisms for acid resistance in bacteria are proton pumping by F1–F0–ATPase, the glutamate decarboxylase system, formation of a protective cloud of ammonia, high cytoplasmic urease activity, repair or protection of macromolecules, and biofilm formation. The field of synthetic biology has rapidly advanced and generated an ever-increasing assortment of genetic devices and biological modules for applications in biofuel and novel biomaterial productions. Better understanding of aspects such as overproduction of general shock proteins, molecular mechanisms, and responses to cell density adopted by microorganisms for survival in low pH conditions will prove useful in synthetic biology for potential industrial and environmental applications.